Microporous, Self-Segregated, Graphenal Polymer Nanosheets Prepared by Dehydrogenative Condensation of Aza-PAHs Building Blocks in the Solid State - Fuyu Yuan (2018)
© 2017 American Chemical Society. A class of porous organic polymers (POPs), which are constructed by aryl-aryl linkages, has the wholly conjugated organic frameworks that can post-transform into two-dimensional graphenal polymers by the intramolecular dehydrogenation. However, typical examples are difficultly defined on the molecular sizes, numbers, and distributions of graphene subunits within the networks, thereby giving rise to uncertainty in applications. Here we report a dehydrogenation fusion of polycyclic aromatic hydrocarbons (PAHs) into graphenal polymers under solvent-free and ionothermal conditions, by which 5,6,11,12,17,18-hexaazatrinaphthylene (HATNA) is linked on itself to expand along the coplanar direction. During the reaction, the catalyst AlCl3solids turn into the molten media to homogenize the reaction system, and alter the molecular configuration and reactivity of HATNA units, resulting in the formation of self-segregated nanosheets with the neighboring layers of the weakened π-π interaction. Besides, the obtained framework exhibits the intrinsic microporosity and exceptionally high surface area. We demonstrate that they can well perform on anhydrous proton conduction and catalytic cycloaddition of CO2with epoxides. Therefore, this bottom-up strategy may constitute a step toward realizing innovative applications of POPs based on commercially available PAHs.